Longitudinal Characterization of Coccidiosis Control Methods on Live Performance and Nutrient Utilization in Broilers - Gautier, Alyson E.; Latorre, Juan D.; Matsler, Phil L.; Rochell, Samuel J. (Frontiers in Veterinary Science, 2020)
An experiment was conducted to quantify the timing and magnitude of potential losses in growth performance, apparent ileal digestibility (AID) of nutrients and energy (IDE), and intestinal morphology for broilers vaccinated for the control of coccidiosis compared with those provided a chemical coccidiostat. Treatment groups consisted of 3 coccidiosis control methods: unvaccinated, unmedicated (NC), in-feed chemical coccidiostat (PC), and live oocyst vaccination (VAC) at day of hatch and were administered to male Cobb broilers reared in floor pens. Body weight gain (BWG), feed intake (FI), and feed conversion ratio (FCR) were determined at 12, 16, 20, 28, and 36 d. Blood and ileal digesta were collected from birds in 10 replicate pens of each treatment at 12, 16, 20, and 36 d to evaluate plasma carotenoid and nitric oxide concentrations and determine nutrient AID and IDE. Jejunal samples were taken at 12, 20, and 36 d for morphological measurements. Oocyst shedding in VAC birds was confirmed by increased oocyst counts and decreased carotenoid concentrations (P < 0.05) when compared with PC birds, with no differences (P > 0.05) in nitric oxide concentrations. At 20 d, BWG and FI were lowest (P < 0.05) in VAC birds, intermediate in NC birds, and highest in PC birds, with no differences in FCR (P > 0.05). By 28 and 36 d, FCR was higher (P < 0.05) for VAC and NC birds but BWG and FI of VAC birds were similar (P > 0.05) to PC birds. At d 12, IDE and AID of nitrogen and ether extract were lower (P < 0.05) in VAC birds than PC birds. At d 16, AID of nitrogen was similar (P > 0.05) between PC and VAC birds, whereas AID of ether extract remained lower in VAC birds than PC birds. No differences in AID of nutrients or IDE were observed (P > 0.05) between VAC and PC birds at 20 or 36 d. No differences (P > 0.05) in jejunal morphology were observed at any time point. Overall, VAC elicited a transient reduction in AID and IDE, particularly for lipids, that diminished by d 20.